2013
DOI: 10.1002/ird.1782
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Water Flow and Salt Leaching Under Sequential Flooding Between Subsurface Drains

Abstract: Streamline behaviour and solute transport were investigated under sequential flooding situations using a HYDRUS‐2D/3D model. HYDRUS‐simulated solute breakthrough curves exhibit a similar shape as measured curves but breakthrough is slightly delayed. This might be caused by slightly different properties (particularly particle size distribution) of silica sand used to determine solute transport and van Genuchten parameters. The breakthrough curves for comparable flooding scenarios under both lower and upper drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Progressive ponding enhances the local hydraulic head gradient in the interior. The leaching efficiency can be thus improved by up to 4 times with respect to the amount of water needed to drain the soil to the required soil depth [16,17]. While salt transport in the soil is affected by both advection and diffusion/dispersion processes, all these studies suggested that increasing the hydraulic head gradient between the drain and interior is the key to improving the efficiency of salt leaching.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive ponding enhances the local hydraulic head gradient in the interior. The leaching efficiency can be thus improved by up to 4 times with respect to the amount of water needed to drain the soil to the required soil depth [16,17]. While salt transport in the soil is affected by both advection and diffusion/dispersion processes, all these studies suggested that increasing the hydraulic head gradient between the drain and interior is the key to improving the efficiency of salt leaching.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The salt leaching method has been studied extensively via analytical solutions [7][8][9][10], laboratory experiments [11,12], field investigations [13][14][15] and numerical simulations [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Arid regions are susceptible to high risk of salinization, which is mainly caused by the high evaporation rates as well as the retarded leaching characteristics of the soils in these areas. Irrigation is a major factor affecting soil salinity, and salts enter into the soil through applied water and accumulate in the root zone because of inadequate leaching (Mirjat et al 2014). In addition, excessive irrigation can lead to a rise in the water table.…”
Section: Introductionmentioning
confidence: 99%
“…During irrigating, solute salt in irrigation water accumulates in soils and gradually stores at the root zone by root water uptake. Besides, soil evaporation mainly occurs between mulches, and salts usually accumulate along the wetting fronts and the bare soil belts, which always lead to soil salinization (Mirjat et al, 2014) and affects the sustainable utilization of brackish water (Aragüés et al, 2015). With the years of increasing mulched drip irrigation with brackish water, the depth of 30 ~ 60 cm is the main 4 / 46 part of salt accumulation (Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%